2012
DOI: 10.1364/ao.51.000535
|View full text |Cite
|
Sign up to set email alerts
|

Image degradation due to surface scatter in the presence of aberrations

Abstract: Image analysis in the presence of surface scatter due to residual optical fabrication errors is often perceived to be complicated, nonintuitive, and achieved only by computationally intensive nonsequential ray tracing with commercial optical analysis codes such as ASAP, Zemax, Code V, TracePro, or FRED. However, we show that surface scatter can be treated very similarly to conventional wavefront aberrations. For multielement imaging systems degraded by both surface scatter and aberrations, the composite point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The surface geometry and roughness establish a value of reflectance that plays an important role when observing objects through a microscope. Accurate reflectance numerical modeling is still a challenging problem, especially in computer graphics for generating realistic images of scenes or for predicting image degradation in optical mirror surfaces, because it requires computational intensive methods like the Beckmann-Kirchhoff theory for rough surface reflectance or the generalized Harvey-Shack surface scatter theory [23,24]. However, the purpose of our simulations is to evaluate the performance of different 3D reconstruction methods under surfaces of variable reflectance.…”
Section: A3 Reflectance Mapsmentioning
confidence: 99%
“…The surface geometry and roughness establish a value of reflectance that plays an important role when observing objects through a microscope. Accurate reflectance numerical modeling is still a challenging problem, especially in computer graphics for generating realistic images of scenes or for predicting image degradation in optical mirror surfaces, because it requires computational intensive methods like the Beckmann-Kirchhoff theory for rough surface reflectance or the generalized Harvey-Shack surface scatter theory [23,24]. However, the purpose of our simulations is to evaluate the performance of different 3D reconstruction methods under surfaces of variable reflectance.…”
Section: A3 Reflectance Mapsmentioning
confidence: 99%
“…Choi and Harvey [31], showed that, for multi-element imaging systems degraded by both surface scatter and aberrations, the composite PSF is obtained in explicit analytic form in terms of convolutions of the geometrical PSF and scaled BRDFs of the individual surfaces of the imaging system. And a recent parametric analysis of the effect of scattered light upon the MTF of an imaging system discussed in some detail the situations under which Eq.…”
Section: System Mtf In the Presence Of Surface Scattermentioning
confidence: 99%
“…The quality of the images captured in professional astronomy is of vital importance to the scientific community, so a high degree of accuracy is required in the technology used to take them [ 1 , 2 , 3 , 4 , 5 ]. This technology, in addition to providing images of the highest possible quality through their respective charge-coupled devices (CCDs), must be able to mitigate all sources of noise that cause a loss of image quality.…”
Section: Introductionmentioning
confidence: 99%